Professional women's information needs in developing countries: ICT as a catalyst (2003)
Women form half of the world population, and they require information because as human beings it empowers them to make informed decisions based on the knowledge at their disposal. The availability of information and its use of paramount importance to any group of people. The paper dicusses the special information needs of professional women. It focuses on women lawyers, journalist, librarians, doctors, pharmacist, engineers, bankers, information scientists and architects in Nigeria. Thier general information needs can be basic, but speical needs such as social domestic, economic, personal, professional, political, medical and religious are examined, while the impact information has on them is reviewed. An attempt is made to analyze the peculiarity of professional women information needs in view of their status and profile. The importance of Information and Communication Technologies (ICTs) in attaining the goal of satisfying the information seeking behaviour of these women professionals is noted, especially in a developing country like Nigeria. Information Technology(IT) can offer significant opportunities for virtually all girls and women in developing countries, including poor living in rural areas but the availability of such facilities is only limited to the urban areas. According to research,the exposure and ability to sue the facilitoes was noted to be an exclusive advantage of educated elite women because of thier educational background. Studies show that home access to a compture and the internet is uncommon in developing countries and the professional women desire to be more adequately informed, thus the need for greater access is most required. Questionnaire and interview methods were used for data gathering. Respondents were contacted mainly through thier professional bodies. Data analysis was done using the statistical package for the social sciences for windows. Recommendations are made as to how women professionals in developing countries who lack ICT facilities can network with ither groups.